2009
DOI: 10.1194/jlr.m800551-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Plasma apolipoprotein AV levels in mice are positively associated with plasma triglyceride levels

Abstract: Apolipoprotein AV (apoAV) overexpression causes a decrease in plasma triglyceride (TG) levels, while deficiency of apoAV causes hypertriglyceridemia in both men and mice. However, contrary to what would be expected, plasma apoAV and TG levels in humans are positively correlated. To address this apparent paradox, we determined plasma apoAV levels in various mouse models with median TG levels ranging from 30 mg/dl in wild-type mice to 2089 mg/dl in glycosylphosphatidylinositol-anchored HDL binding protein 1-defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…In humans, several loss-of-function and null apoA-V alleles are associated with both reduced plasma apoA-V levels and elevated plasma TG ( 12, 13 ), yet other studies have found both positive and negative associations between plasma apoA-V and TG concentrations ( 7,14,15 ). Moreover, recent studies in mice have found a positive correlation between plasma apoA-V and TG concentrations ( 16,17 ).Despite its apparent impact on intravascular TG-rich lipoprotein lipolysis and clearance, a peculiar characteristic of apoA-V is that its plasma concentration is in the range of 100-200 µg/l, which is ‫ف‬ 10,000-fold lower than apoA-I and ‫ف‬ 1,000-fold lower than apoA-IV and corresponds to ‫ف‬ 1 molecule of apoA-V for every 1,000 VLDL particles ( 18,19 ). This presents a conundrum as to how an apolipoprotein circulating at such low levels could exert such a potent effect on plasma TG metabolism and concentration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In humans, several loss-of-function and null apoA-V alleles are associated with both reduced plasma apoA-V levels and elevated plasma TG ( 12, 13 ), yet other studies have found both positive and negative associations between plasma apoA-V and TG concentrations ( 7,14,15 ). Moreover, recent studies in mice have found a positive correlation between plasma apoA-V and TG concentrations ( 16,17 ).Despite its apparent impact on intravascular TG-rich lipoprotein lipolysis and clearance, a peculiar characteristic of apoA-V is that its plasma concentration is in the range of 100-200 µg/l, which is ‫ف‬ 10,000-fold lower than apoA-I and ‫ف‬ 1,000-fold lower than apoA-IV and corresponds to ‫ف‬ 1 molecule of apoA-V for every 1,000 VLDL particles ( 18,19 ). This presents a conundrum as to how an apolipoprotein circulating at such low levels could exert such a potent effect on plasma TG metabolism and concentration.…”
mentioning
confidence: 99%
“…In humans, several loss-of-function and null apoA-V alleles are associated with both reduced plasma apoA-V levels and elevated plasma TG ( 12, 13 ), yet other studies have found both positive and negative associations between plasma apoA-V and TG concentrations ( 7,14,15 ). Moreover, recent studies in mice have found a positive correlation between plasma apoA-V and TG concentrations ( 16,17 ).…”
mentioning
confidence: 99%
“…In vivo data suggest an apoA-V-mediated faster removal of TG-rich lipoproteins rather than an increased production mechanism (Kluger et al, 2008). Vaessen and coworkers believe that higher plasma apoA-V levels reflect an increased demand for plasma TG hydrolysis under physiological conditions in mice (Vaessen et al, 2009 the presence of a high concentration of recombinant apoA-V (600 mg/ml). It was thought that apoA-V at high concentrations might produce non-specific hydrophobic interactions increasing hydrolysis or stabilizing functional LPL in vitro (Merkel et al, 2005).…”
Section: Discussionmentioning
confidence: 95%
“…Mice overexpressing human apoA-V showed a decrease in plasma TG levels to one-third of those in control littermates; whereas, apoA-V knockout (apoA-V -/-) mice had approximately four times higher plasma TG levels than that of control littermates (Pennacchio et al, 2001). In wild-type and Gpihbp1 -/-mice with median TG levels, the apoA-V and TG levels are reported to be positively correlated suggesting that higher plasma apoA-V levels reflect an increased demand for plasma TG hydrolysis under physiological conditions (Vaessen et al, 2009). Although the relationship between apoA-V and plasma TG has been well characterized, little is known about its effects on lipoprotein metabolism and other functions aside from modulating TG homeostasis.…”
Section: Introductionmentioning
confidence: 89%
“…Severely elevated plasma TG and reduced clearance of apoA-V in GPIHBP1 deficiency are not specific to this metabolic aberration. Vaessen et al [21] examined plasma TG and apoA-V levels in lpl −/− mice and noted a parallel elevation of TG and apoA-V. LPL gene transfer into LPL deficient mice resulted in a simultaneous decrease in TG and apoA-V. Thus, hydrolysis of TG-rich lipoproteins is necessary for normal clearance of apoA-V transported on CM and VLDL.…”
Section: Glycosylphosphatidylinositol-anchored High Density Lipoprmentioning
confidence: 99%